Kounis Syndrome Presenting as Very Late Stent Thrombosis in an Everolimus-Eluting Stent Following Wasp Stings - Min, Jung Hwa; Kang, Min-Ho (Korean circulation journal, 2013)
Kounis syndrome is the concurrence of acute coronary syndromes with conditions associated with mast cell activation following an allergic insult. We report a 56-year-old man who experienced a ST-segment elevation myocardial infarction after wasp stings. The patient presented without signs of anaphylaxis or shock. Coronary angiography showed an everolimus-eluting stent thrombosis (ST) of the left anterior descending artery occluding the vessel completely which was deployed for stable angina 3 years ago. The patient had been compliant with anti-platelet therapy, and no relevant cardiovascular events occurred until the day of admission. We interpreted our patient's condition as a manifestation of Kounis syndrome. To our knowledge, this is the first case of Kounis syndrome showing very late ST in a second-generation drug-eluting stent caused by wasp stings.